Investigation of pyrolysis kinetics, thermodynamics, product characteristics and reaction mechanism of rubber seed oil. (15th September 2021) - Chen, Fangjun; Zhang, Fengxia; Yang, Shiliang; Liu, Huili; Wang, Hua; Hu, Jianhang
Graphical abstract: Highlights: Pyrolysis experiments of RSO were performed by TGA and down tube reactor. Model-free and model-fitting methods were utilized to calculate pyrolysis kinetics. Pyrolysis of RSO followed 1.5-order of reaction model. Liquid products contained large amounts of oxygenated compounds. The pyrolysis reaction mechanism of RSO was proposed. Abstract: Rubber seed oil (RSO) is a non-edible oil extracted from a by-product of the rubber industry (rubber seed), which is a potentially renewable resource that can be converted into various fuels/fuel precursors and high-value chemicals through pyrolysis. In the current work, the pyrolysis kinetics, thermodynamics, product characteristics and reaction mechanism of RSO were comprehensively investigated by a thermogravimetric analyzer and a down tube reactor. Two model-free methods (Flynn-Wall-Ozawa method and Kissinger-Akahira-Sunose method) were used to calculate the apparent activation energy at different conversion rates, which were distributed between 176.77 and 292.57 kJ/mol. The apparent activation energy of RSO was calculated using the model-fitting methods based on 16 commonly used models, and the results varied greatly by different models. The 1.5-order of reaction can well explain the pyrolysis process of RSO. The analysis of pyrolysis products showed that the gas products were mainly CO2, CO, H2 and CH4 and other small molecules of hydrocarbons, liquid products mainly contained alkanes, alkenes, monocyclic aromatic hydrocarbons, polycyclic aromatic hydrocarbons and other oxygenated organics, the microscopic morphology of coke was spherical carbon particles with different sizes. Finally, the pyrolysis mechanism of RSO was discussed based on the information of the products. These findings will provide helpful information for the design of pyrolytic process using rubber seed oil as a feedstock.